Ab Initio Study of the Large Amplitude Motions of Various Monosubstituted Isotopologues of Methylamine (CH3-NH2) - Al-Mogren, Muneerah Mogren; Senent, María Luisa (Frontiers in Chemistry, 2021)
CCSD(T)-F12 theory is applied to determine electronic ground state spectroscopic parameters of various isotopologues of dimethylamine (CH3-NH2) containing cosmological abundant elements, such as D, 13C and 15N. Special attention is given to the far infrared region. The studied isotopologues can be classified in the G12, G6 and G4 molecular symmetry groups. The rotational and centrifugal distortion constants and the anharmonic fundamentals are determined using second order perturbation theory. Fermi displacements of the vibrational bands are predicted. The low vibrational energy levels corresponding to the large amplitude motions are determine variationally using a flexible three-dimensional model depending on the NH2 bending and wagging and the CH3 torsional coordinates. The model has been defined assuming that, in the amine group, the bending and the wagging modes interact strongly. The vibrational levels split into six components corresponding to the six minima of the potential energy surface. The accuracy of the kinetic energy parameters has an important effect on the energies. Strong interactions among the large amplitude motions are observed. Isotopic effects are relevant for the deuterated species.